Which Arabic Dialect Are Swahili Words From? - Brook, Zev (Studia Orientalia Electronica, 2022)
This article investigates the Arabic component of the Standard Swahili lexicon, aiming to identify the Omani Arabic dialect which comprises the dominant donor of loanwords to Swahili. I isolate words from this “donor dialect” from other Arabic dialects that have influenced Swahili, and compare this lexical archive with data on the dialectology of Omani Arabic phonology and verbal morphology. I find that, contrary to widespread assumptions, documented Arabic from Oman’s mountainous interior, the source region of Omani settlers, has significant differences from the donor dialect. This holds true for fieldwork done in the nineteenth century and in the twenty-first. I characterize the donor dialect to the fullest extent possible, given the Swahili data, and find that it is closest to modern Zanzibari Arabic, which may be its descendant. I proceed to review how a better understanding of the donor dialect can clear up errors made in the literature of Swahili history and historical linguistics, and finally provide etymologies for twenty-two Swahili words that are likely borrowings from Omani Arabic but frequently attributed to other sources, due to being borrowings within Omani Arabic itself.